Australian Dance Theatre National Theatre May 8 - 16 - Gaica, Branco, 1950- ([Australia] : Australian Dance Theatre)
Shows a photographic image of a woman embracing a man, with her head against his shoulder. Background of horizontal lines.
"Book now at Bass/J.C.W./National Theatre".
Catalogue record generated as part of a batch load.
Australian Dance Theatre
Also available online
Keywords: Australian Dance Theatre -- Posters; Dance companies -- Australia -- Posters; Modern dance -- Australia -- Posters